CORRELATION STUDY OF CHURCH LEADERSHIP TOWARDS CHURCH MEMBER COMMITMENT IN CHRISTIAN CHURCH OF INDONESIA DARMO SATELIT SURABAYA-JAWA TIMUR - Permana, Surja; Lambertus Lontoh, Frederich Oscar; Kusuma, Samuel; Verhezen, Peter; Lily, Tabitha (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
This research is based on a phenomenon where Christians feel they are free to choose where they want to go to worship every Sunday, going to church but without commitment and special involvement with the church where they worship. The present church's meaning moves to deviate from mutual communal worship activities to individualist choices and tastes. This research was conducted at Indonesian Christian Church in Indonesian Christian Church Darmo Satelit Surabaya domiciled in Surabaya, East Java to 100 congregations as research respondents by describing the influence between church leadership variable toward the commitment of congregation. The findings of this study are the influence of church leadership on the commitment of the congregation is positive with a value of 0.590 in the category of moderate and the regression equation is Å¶ = 33.887 + 0.818 X, which means that each increase of leadership style per-unit will increase the commitment of the congregation of 0.818 times.